Presentasi Efektif untuk Siswa SMA: Membangun Kepercayaan Diri dan Teknik Berbicara di Depan Umum - Mardhiyyah, Mardhiyyah; Sulistyo, Ponco Budi; Putra, Afdal Makkuraga (MENARA RIAU, 2025)
Public speaking and presentation skills are essential skills for high school students, both in academics and in preparation for future careers. However, many students have difficulty conveying ideas effectively due to a lack of self-confidence and good speaking techniques. This Community Service Activity aims to improve the presentation skills of high school students in the Tangerang City Area through systematic public speaking training. The outputs of the activity include increased student self-confidence, improved mastery of presentation techniques, and enhanced verbal and non-verbal communication skills in preparation for presentations and public speaking.